Total quality management in education - Mukhopadhyay, Marmar (SAGE Publications India Pvt. Ltd., 2020)
"This is a complete revised edition of a popular text on Total Quality Management (TQM). First published in 2001, the book has been translated into many languages and highly praised by readers globally. In spite of the difficulties in defining and capturing 'quality' in a framework, the author admirably succeeds in helping readers to understand the role of TQM in improving the quality of education. The book combines extensive literature review with the author's own experience as an institution builder and his experiments on quality management to develop a practical guide for quality improvement for institutional leaders. The book introduces Shewhart, Lewin, Deming, Juran, Crosby, Ishikawa, Taguchi and a number of other quality gurus to the readers. It proposes a new set of TQM principles that a good leader should apply. Enriched with several examples from the field situation and local metaphors, Total Quality Management in Education is an easy read and a must-have practical guide to quality management"--